2016
DOI: 10.1177/0095798416649086
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Our Understanding of Eating Practices, Body Image, and Appearance in African American Women: A Qualitative Study

Abstract: Researchers consistently have supported the notion that African American women experience greater body satisfaction and are less likely to engage in unhealthy restrictive eating practices due to broader and more flexible body image norms in the African American community. Yet empirical evidence also suggests that African American women experience high rates of binge-eating behaviors and obesity. The purpose of this qualitative study was to gain a deeper understanding of the factors that influence body image no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In other studies, however, African American women reported ambivalence (Baturka, Hornsby, & Schorling, 2000;Watson, Ancis, White, & Nazari, 2013) as well as body dissatisfaction (Fitzgibbon, Blackman, & Avellone, 2000;Talleyrand, Gordon, Daquin, & Johnson, 2017). For example, mothers report feeling anxiety over children's weight even if they do not use the term "obese" to describe them (Hughes, Sherman, & Whitaker, 2010).…”
Section: African American Views On Weight and Attractivenessmentioning
confidence: 90%
“…In other studies, however, African American women reported ambivalence (Baturka, Hornsby, & Schorling, 2000;Watson, Ancis, White, & Nazari, 2013) as well as body dissatisfaction (Fitzgibbon, Blackman, & Avellone, 2000;Talleyrand, Gordon, Daquin, & Johnson, 2017). For example, mothers report feeling anxiety over children's weight even if they do not use the term "obese" to describe them (Hughes, Sherman, & Whitaker, 2010).…”
Section: African American Views On Weight and Attractivenessmentioning
confidence: 90%
“…However, these ideals may become detrimental as they come in contact with the increasing globalization of food systems coupled with the massive marketing of obesogenic foods, and the technological transition aiding the preponderance of sedentary lifestyles [35]. In other communities where large body size ideals have been observed, such as the African American community in the United States, the prevalence of obesity among women was greater than that of other racial groups [3638]. Additionally, the presence of HIV stigma and the notion that thinness and weight loss were associated with HIV infection within SSA countries may exacerbate the situation: as we noted in the qualitative synthesis that overweight women were reluctant to lose weight to avoid stigma [17,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination is generally associated with disturbances in eating behavior even after controlling for more general life stressors (Durso, Latner, & Hayashi, 2012). Culturally, however, food has been identified as a source of comfort for Black Americans particularly in times of distress (Talleyrand et al, 2017). Importantly, Black Americans often hold a different cultural worldview than White/European Americans.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have questioned whether the current traditional measures of body ideals/satisfaction truly capture body and appearance concerns for Black American women (Capodilupo & Kim, 2014). Limited research has indicated that psychosocial and contextual factors such as racism and oppression, rather than primarily a desire to be thin, influence conflicting societal expectations of beauty for Black American women, which in turn could also potentially influence body image and stress-related eating patterns among this population (Capodilupo & Kim, 2014;Talleyrand, Gordon, Daquin, & Johnson, 2017). Perhaps the unique and intersecting experience of racism and Africentric identity development that Black American women experience in U.S. society is a missing contributing factor to the racial differences seen in the etiology of eating pathology.…”
Section: Cultural Worldviewmentioning
confidence: 99%